2004
DOI: 10.1111/j.0307-6962.2004.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermoperiods on diapause induction in the cabbage beetle, Colaphellus bowringi (Coleoptera: Chrysomelidae)

Abstract: The effects of thermoperiods on diapause induction in continuous darkness or under a 12 : 12 h LD photoperiod were investigated in the cabbage beetle, Colaphellus bowringi Baly, a typical short-day species. The diapause response curves both at different constant temperatures and at the thermocycle of format CT x: (24 À x) h (16 : 28 C) under continuously dark rearing conditions showed that the incidence of diapause depended mainly on whether or not the mean temperature was 20 C or >20 C. If the mean temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 17 publications
0
24
0
1
Order By: Relevance
“…Thermal response curves of C. bowringi for diapause induction were determined at 12, 16, 24, 28, and 30 °C under DD and LL (Figure 1) for comparison with previous results (Wang et al., 2004b). The response curves showed that temperatures per se could induce diapause in the absence of photoperiodic signals as well as under LL.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…Thermal response curves of C. bowringi for diapause induction were determined at 12, 16, 24, 28, and 30 °C under DD and LL (Figure 1) for comparison with previous results (Wang et al., 2004b). The response curves showed that temperatures per se could induce diapause in the absence of photoperiodic signals as well as under LL.…”
Section: Resultsmentioning
confidence: 75%
“… Thermal response curves for the induction of diapause in the cabbage beetle, Colaphellus bowringi at various constant temperatures under continuous darkness [n = 108–212, after Wang et al. (2004b)] and continuous light (n = 111–183).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations